Micromachines for Biological Micromanipulation - Xu, Qingsong (Springer International Publishing : Imprint: Springer, 2018)
Provides new mechanical designs of microinjectors, microsyringes, microgrippers, and microforce sensors with experimental verifications; Presents new position and force control of the microinjection systems for biological cell microinjection; Examples give the reader more practice in the design, modeling, and control of biological micromanipulation systems. This book provides an overview of the noteworthy developments in the field of micromachining, with a specific focus on microinjection systems used for biological micromanipulation. The author also explores the design, development, and fabrication of new mechanical designs for micromachines, with plenty of examples that elucidate their modeling and control. The design and fabrication of a piezoelectric microinjector, constant force microinjector, constant force microgripper, PDVF microforce sensor, and a piezoelectric microsyringe are presented as examples of new technology for microinjection systems. This book is appropriate for both researchers and advanced students in bioengineering.